A new species of the grenadier genus Coelorinchus (Gadiformes: Macrouridae) from the western Indian Ocean - Prokofiev, Artem M.; Iwamoto, Tomio (Zootaxa, 2022)
A new species, Coelorinchus tricristiger sp. nov., is described from the western Indian Ocean off Socotra and Somalia. It belongs to the Coelorinchus hubbsi group of the subgenus Quincuncia. The modified scales on top of the postorbital portion of head forming a prolonged longitudinal ridge, in combination with its distinctive body markings and the absence of a ventral projection of subopercle, make the new species easily distinguishable from congeners. This is the second representative of the C. hubbsi group in the western Indian Ocean in addition to the previously known C. melanosagmatus.